10 What can we learn from the COVID-19 pandemic about admissions to a hospice IPU?. Issue Volume 11: Issue (2021)Supplement 1 (16th March 2021) - Meeks, Emily; Taylor, Liz
Abstract : Background: The 2020 COVID-19 pandemic has affected how hospices have functioned, with visiting restrictions and perceived public fear of healthcare environments. It was thought that hospice IPU admissions had reduced and that those admitted were further on in their disease trajectory. Aims: To review hospice referrals, admissions, length of stay, care and communication records and mortality during the COVID-19 pandemic and compare it to the previous year. Methods: A retrospective review of the case notes of all admissions to a hospice IPU over a 6-month period from 1st of April to 30th September in 2019 and 2020. Results: There were 97 admissions in 2019 vs 94 in 2020. 44/97 (45%) vs 45/94 (48%) died during admission. The average length of stay was 14.4 days (2019) vs 10.4 (2020) p=0.036, when excluding respite admissions (which had temporarily suspended in 2020) and day procedure admissions the average length of stay was 17.3 days vs 10.3 days, p= 0.0009. Those referred in for end of life care was 27 vs 35. Of those that died during their admission there was no difference in the length of stay 12.2 vs 10.1 days, p=0.41. There was no significant difference in length of stay prior to starting the care and communication record, 9.4 vs 5.6 days, p=0.06. Conclusions: Though there were no differences in numbers of admission during the COVID 19 pandemic. There were significant differences in the length of stay. It was thought that the those coming in during the pandemic were more likely to be coming in for end of life care but as no significant difference between length of stay of patients that died nor in how quickly they were started on the care and communication record this was not the case. This information should be considered when improving current discharge processes.